The Effectiveness of Wordwall Media to Learning Outcomes of Journal Entries for Merchandising Company Class XII IPS SMA Negeri 1 Karanganom - Setiyawan, Yovi Annang; Ulfatun, Titik; Xaphakdy, Sengaloun (Proceedings International Conference on Education Innovation and Social Science, 2022)
Technological developments make activities easy, effective, efficient and fast. This effectiveness is also felt in the world of education, namely the learning media used. One of the effective and easy-to-use learning media in the assessment of learning outcomes is wordwall. This study aims to determine the effectiveness of wordwall media to learning outcomes of merchandising company class XII IPS SMA Negeri 1 Karanganom. This research is a type of quantitative research with a quasi-experimental research method (quasi-experimental). The sampling technique used was non- probability sampling with purposive sampling. The results showed the average value of N-gain percent for the experimental class (wordwall media) was 68.3985 or 68% including quite effective category when compared to the average value of N-gain percent for the control class (conventional media) of 30.9269 or 31% included in the ineffective category. The result of the eta squared calculation is 0.91 which is interpreted as having a moderate effect. The significance value (2-tailed) in the paired t-test is 0.000. It can be interpreted that the value is less than 0.05, which means that there is an effectiveness of wordwall media to learning outcomes of journal entries for merchandising company class XII IPS SMA Negeri 1 Karanganom.